Sunshine Colourful Sdn Bhd / Mohd Subhi Hassan... [et al.] - Hassan, Mohd Subhi; Ismail, Isma Adri; Md Ibrahim, Halijah; Jaafar, Jualiana Zawati; Sahuri, Mohamad Ali (2001)
Sunshine Colourful Sdn Bhd is a printing company that offer various king of printing material such as banner, shirt and stitch. They based in Penang and started their business in the early of 2001.